Creating Cultural and Historical Imaginaries in Physical Space: Worldbuilding in Chinese Theme Parks - Baker, Carissa (SARE: Southeast Asian Review of English, 2021)
Theme parks are fascinating texts built on spatial narratives and detailed storyworlds. Worldbuilding and subcreation are literal in these spaces, but they likewise contain symbolic experiences that represent cultural and historical imaginaries. China is one of the largest markets in the global theme park industry. The design ethos in many parks is to represent fantasy versions of reality or depict cultural beliefs. This article offers analysis of examples in Chinese parks that signify simulated place or culture (for example, Splendid China’s parks), a romanticized historical time (the Songcheng parks), local stories (Sunac Land parks), and national cultural stories (the Fantawild Oriental Heritage model). Each of these spaces presents narratives and immersive environments that have the power to engage visitors on physical, sensual, conceptual, and emotional levels. They are second worlds to play in, imagine in, and to consume fantasy in while also providing a shifting model of theme park experience.